The impact of decriminalization on marijuana and alcohol consumption in Jamaica. Issue 2 (28th November 2019) - Spencer, Nekeisha; Strobl, Eric
Abstract: We examine whether marijuana decriminalization in Jamaica, a country that historically has had relatively widespread use of the drug, has led to an increase in its use, the frequency of use and the money spent on it. To this end, we use a national drug survey dataset with extensive information on people's use of, attitudes towards, access to marijuana. Our econometric analysis shows that awareness of the legislation has a positive correlation with the use of the substance. Worryingly, decriminalization positively correlates with the likelihood of first time and general use for youths. There is also some evidence that the legislation results in a substitution away from alcohol towards marijuana consumption for youths. From a policy perspective, a marijuana monitoring system can be implemented to follow the consumption patterns of youths. This should involve establishing school-level programmes that monitor students, and where potential drug users are identified, school officials should intervene to curb students' drug appetite before an escalated use of marijuana.